The Effect of Customer Satisfaction and Brand Loyalty on Increas-ing Karawo's Business Market Share - Darman (Eastasouth Institute, 2023)
This study aims to examine the effect of consumer satisfaction and brand loyalty on increasing the market share of Karawo Enterprises in Gorontalo. Consumer satisfaction and brand loyalty are im-portant factors in maintaining business continuity and growth. This study uses a quantitative approach with a survey method of 570 Karawo customer respondents in Gorontalo. Data was collected us-ing a questionnaire designed to measure the level of customer satis-faction, brand loyalty, and other factors that could potentially affect market share. Data analysis was performed using multiple linear regression techniques. The results showed that consumer satisfaction has a significant effect on increasing market share. Meanwhile, brand loyalty has no significant effect on increasing market share.